Identification of a highly potent and selective CB2 agonist, RQ-00202730, for the treatment of irritable bowel syndrome. Issue 2 (15th January 2015) - Iwata, Yasuhiro; Ando, Kazuo; Taniguchi, Kana; Koba, Naomi; Sugiura, Akemi; Sudo, Masaki
Graphical abstract